New species of pollen wasps Paramasaris fernandae sp. nov. (Hymenoptera, Vespidae, Masarinae) from a rain forest locality in Brazilian Amazonia - Silveira, Orlando T. (Zootaxa, 2015)
Paramasaris fernandae Silveira, sp. nov. is described from the Brazilian state of Pará, and its affinities with other species in the genus are discussed. Record of this new species greatly expands geographical range of occurrences for Paramasaris Cameron as a whole, and in a kind of forest habitat unusual for the group.